Management of SAM Children in India: Current Strategies - Kapil, Umesh (Indian Journal of Community Health, 2015)
Management of children with Severe Acute Malnutrition (SAM) is being given a high priority in India. This intervention is being implemented for bringing reduction in under five mortality. Children with SAM are 9 times higher risk of mortality as compared to optimally nourished children. There are two strategies for management of Children with SAM namely i) Facility based and ii) Community Based. More than 90% of children can be treated through community based management. The progress of facility based management has been satisfactory in India. However, the programme of community based intervention is slow due to lack of scientific data on impact of indeginous RUTF available in the country. The scientific evidence is being generated through sponsored research studies so that evidence based management of SAM children can be developed.